2018
DOI: 10.20527/jht.v5i2.4364
|View full text |Cite
|
Sign up to set email alerts
|

POTENSI KELEMBAGAAN LOKALDALAM PENGELOLAAN DAERAH ALIRAN SUNGAI (Studi Kasus di Desa Cemplang

Abstract: Watershed Management becomes an important aspect in supporting the conservation of the surrounding area. Upstream area functions as a water catchment area must be kept by maintaining the utilization of the area to avoid the carrying capacity beyond the environment. The role of people in the surrounding area becomes an important effort to maintain the continuity of the function of the Watershed. This study aims to analyze the potency of local institutional support in watershed management. The research method is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Based on the identification, institutional problems in the Lake Toba catchment management include issues of legality and planning integration, legal power of institutions, coordination and collaboration of parties, and commitment of regional stakeholders to integrate environmental conservation programs into their regional programs. The study also showed that the failure of watershed management in Indonesia is the result of the non-integration of activities [12,13,14] and weak coordination among institutions [14,15,16]. In terms of planning documents, the management of the Lake Toba catchment requires an integrated plan that is referred to by each institution in carrying out activities.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the identification, institutional problems in the Lake Toba catchment management include issues of legality and planning integration, legal power of institutions, coordination and collaboration of parties, and commitment of regional stakeholders to integrate environmental conservation programs into their regional programs. The study also showed that the failure of watershed management in Indonesia is the result of the non-integration of activities [12,13,14] and weak coordination among institutions [14,15,16]. In terms of planning documents, the management of the Lake Toba catchment requires an integrated plan that is referred to by each institution in carrying out activities.…”
Section: Discussionmentioning
confidence: 99%
“…Hingga saat ini kesepakatankesepakatan dalam mengelola hutan dibuat dalam suatu wadah organisasi yang tepat. Menurut Salampessy (2017), sasaran yang ingin dicapai dari kegiatan pengembangan kelembagaan adalah tumbuhnya kelembagaan yang tangguh, dinamis, dan berdaya saing serta mandiri dalam melakukan pengelolaan lingkungan.…”
Section: Potensi Keterlibatan Masyarakat Lokal Dalam Pengelolaan Huta...unclassified
“…As was done by other researchers [5] who also studied community participation in the development of the Kandri tourism village in Semarang City and produced a form of community participation, pseudo participation is based on contributions to efforts to develop the Kandri tourism village, receiving benefits equally, and decision making concerning the implementation of the tourism village development program, while for the level of community participation it is at the Citizen Power level. Therefore, in tourism activities, the role of the community is very important in developing the tourism potential of the tourism village [8]; [15]; [16].…”
Section: = ℎℎ −mentioning
confidence: 99%